Metabolic Profiles in Cell Lines Infected with Classical Swine Fever Virus - Gou, Hongchao; Zhao, Mingqiu; Yuan, Jin; Xu, Hailuan; Ding, Hongxing; Chen, Jinding (Frontiers in Microbiology, 2017)
Viruses require energy and biosynthetic precursors from host cells for replication. An understanding of the metabolic interplay between classical swine fever virus (CSFV) and host cells is important for exploring the complex pathological mechanisms of classical swine fever (CSF). In the current study, and for the first time, we utilized an approach involving gas chromatography coupled with mass spectrometry (GC-MS) to examine the metabolic profiles within PK-15 and 3D4/2 cells infected with CSFV. The differential metabolites of PK-15 cells caused by CSFV infection mainly included the decreased levels of glucose 6-phosphate [fold change (FC) = -1.94)] and glyceraldehyde-3-phosphate (FC = -1.83) during glycolysis, ribulose 5-phosphate (FC = -1.51) in the pentose phosphate pathway, guanosine (FC = -1.24) and inosine (FC = -1.16) during purine biosynthesis, but the increased levels of 2-ketoisovaleric acid (FC = 0.63) during the citrate cycle, and ornithine (FC = 0.56) and proline (FC = 0.62) during arginine and proline metabolism. However, metabolite changes caused by CSFV infection in 3D4/2 cells included the reduced glyceraldehyde-3-phosphate (FC = -0.77) and pyruvic acid (FC = -1.42) during glycolysis, 2-ketoglutaric acid (FC = -1.52) in the citrate cycle, and the elevated cytosine (FC = 2.15) during pyrimidine metabolism. Our data showed that CSFV might rebuild cellular metabolic programs, thus aiding viral replication. These findings may be important in developing targets for new biomarkers for the diagnosis and identification of enzyme inhibitors or metabolites as antiviral drugs, or screening viral gene products as vaccines.